Analysis of β-Catenin Signalling Activity Suggests Differential Regulation of Ontogenetically Distinct Dentate Granule Neuron Populations - Billmann, Charlotte; Schäffner, Iris; Heppt, Jana; Lie, Dieter Chichung (International Journal of Developmental Neuroscience, 2025)
In mammals, the dentate gyrus of the hippocampus is one of the few regions where neurogenesis continues throughout life. As a result, the dentate gyrus harbours neurons of ontogenetically different origin. Notably, ontogenetically different dentate granule neurons (DGNs) are morphologically distinct and fulfil specialized functions in hippocampal information processing and plasticity. Development of adult-born DGNs is tightly controlled by signals released by the complex cellular environment of the adult dentate gyrus. In mice, an adult-like cytoarchitecture of the dentate gyrus is observed only after postnatal Week 2. The question therefore arises when the signalling environment controlling adult neurogenesis is established and whether development of ontogenetically distinct DGNs is subject to the same regulatory pathways. Here, we analyse BATGAL reporter mice to determine the temporal development of β-catenin-signalling activity in the murine DGN lineage. We show that the β-catenin-signalling pattern, which is essential for precise dendritogenesis and neuronal maturation in adulthood, emerges only around 2 weeks after birth and continues to be refined over the next weeks. These results indicate that the signalling environment controlling adult neurogenesis is only gradually established and suggest that the development of ontogenetically distinct DGNs is controlled by different mechanisms.
CRIS-Team Scopus Importer:2025-02-28
Keywords: dentate gyrus; neurogenesis; niche; β-catenin signalling

Autophagy inhibition promotes SNCA/alpha-synuclein release and transfer via extracellular vesicles with a hybrid autophagosome-exosome-like phenotype - Minakaki, Georgia; Menges, Stefanie; Kittel, Agnes; Emmanouilidou, Evangelia; Schäffner, Iris; Barkovits, Katalin; Bergmann, Anna; Rockenstein, Edward; Adame, Anthony; Marxreiter, Franz; Mollenhauer, Brit; Galasko, Douglas; et al. (Autophagy, 2017)
The autophagy-lysosome pathway (ALP) regulates intracellular homeostasis of the cytosolic protein SNCA/alpha-synuclein and is impaired in synucleinopathies, including Parkinson disease and dementia with Lewy bodies (DLB). Emerging evidence suggests that ALP influences SNCA release, but the underlying cellular mechanisms are not well understood. Several studies identified SNCA in exosome/extracellular vesicle (EV) fractions. EVs are generated in the multivesicular body compartment and either released upon its fusion with the plasma membrane, or cleared via the ALP. We therefore hypothesized that inhibiting ALP clearance 1) enhances SNCA release via EVs by increasing extracellular shuttling of multivesicular body contents, 2) alters EV biochemical profile, and 3) promotes SNCA cell-to-cell transfer. Indeed, ALP inhibition increased the ratio of extra- to intracellular SNCA and upregulated SNCA association with EVs in neuronal cells. Ultrastructural analysis revealed a widespread, fused multivesicular body-autophagosome compartment. Biochemical characterization revealed the presence of autophagosome-related proteins, such as LC3-II and SQSTM1. This distinct "autophagosome-exosome-like" profile was also identified in human cerebrospinal fluid (CSF) EVs. After a single intracortical injection of SNCA-containing EVs derived from CSF into mice, human SNCA colocalized with endosome and neuronal markers. Prominent SNCA immunoreactivity and a higher number of neuronal SNCA inclusions were observed after DLB patient CSF EV injections. In summary, this study provides compelling evidence that a) ALP inhibition increases SNCA in neuronal EVs, b) distinct ALP components are present in EVs, and c) CSF EVs transfer SNCA from cell to cell in vivo. Thus, macroautophagy/autophagy may regulate EV protein composition and consequently progression in synucleinopathies.
EVALuna2:4781

Differential vulnerability of adult neurogenic niches to dosage of the neurodevelopmental-disorder linked gene Foxg1 - Schäffner, Iris; Wittmann, Marie-Theres; Vogel, Tanja; Lie, Dieter Chichung (Molecular Psychiatry, 2022)
The transcription factor FOXG1 serves pleiotropic functions in brain development ranging from the regulation of precursor proliferation to the control of cortical circuit formation. Loss-of-function mutations and duplications of FOXG1 are associated with neurodevelopmental disorders in humans illustrating the importance of FOXG1 dosage for brain development. Aberrant FOXG1 dosage has been found to disrupt the balanced activity of glutamatergic and GABAergic neurons, but the underlying mechanisms are not fully understood. We report that FOXG1 is expressed in the main adult neurogenic niches in mice, i.e. the hippocampal dentate gyrus and the subependymal zone/olfactory bulb system, where neurogenesis of glutamatergic and GABAergic neurons persists into adulthood. These niches displayed differential vulnerability to increased FOXG1 dosage: high FOXG1 levels severely compromised survival and glutamatergic dentate granule neuron fate acquisition in the hippocampal neurogenic niche, but left neurogenesis of GABAergic neurons in the subependymal zone/olfactory bulb system unaffected. Comparative transcriptomic analyses revealed a significantly higher expression of the apoptosis-linked nuclear receptor Nr4a1 in FOXG1-overexpressing hippocampal neural precursors. Strikingly, pharmacological interference with NR4A1 function rescued FOXG1-dependent death of hippocampal progenitors. Our results reveal differential vulnerability of neuronal subtypes to increased FOXG1 dosage and suggest that activity of a FOXG1/NR4A1 axis contributes to such subtype-specific response.
CRIS-Team WoS Importer:2022-04-08

Enhanced mitochondrial fusion during a critical period of synaptic plasticity in adult-born neurons - Kochan, Sandra M.V.; Malo, Meret Cepero; Jevtic, Milica; Jahn-Kelleter, Hannah M.; Wani, Gulzar A.; Ndoci, Kristiano; Pérez-Revuelta, Laura; Gaedke, Felix; Schäffner, Iris; Lie, Dieter Chichung; Schauss, Astrid; Bergami, Matteo (Neuron, 2024)
Integration of new neurons into adult hippocampal circuits is a process coordinated by local and long-range synaptic inputs. To achieve stable integration and uniquely contribute to hippocampal function, immature neurons are endowed with a critical period of heightened synaptic plasticity, yet it remains unclear which mechanisms sustain this form of plasticity during neuronal maturation. We found that as new neurons enter their critical period, a transient surge in fusion dynamics stabilizes elongated mitochondrial morphologies in dendrites to fuel synaptic plasticity. Conditional ablation of fusion dynamics to prevent mitochondrial elongation selectively impaired spine plasticity and synaptic potentiation, disrupting neuronal competition for stable circuit integration, ultimately leading to decreased survival. Despite profuse mitochondrial fragmentation, manipulation of competition dynamics was sufficient to restore neuronal survival but left neurons poorly responsive to experience at the circuit level. Thus, by enabling synaptic plasticity during the critical period, mitochondrial fusion facilitates circuit remodeling by adult-born neurons.
CRIS-Team Scopus Importer:2024-05-31
Keywords: adult neurogenesis; competition; experience; hippocampus; LTP; Mfn2; mitochondria; mitochondrial fusion; neural stem cell; synaptic plasticity

FoxO Function Is Essential for Maintenance of Autophagic Flux and Neuronal Morphogenesis in Adult Neurogenesis - Schäffner, Iris; Minakaki, Georgia; Khan, M. Amir; Balta, Elli-Anna; Schlötzer-Schrehardt, Ursula; Schwarz, Tobias J.; Beckervordersandforth, Ruth; Winner, Beate; Webb, Ashley E.; Depinho, Ronald A.; Paik, Jihye; Wurst, Wolfgang; et al. (Neuron, 2018)
Autophagy is a conserved catabolic pathway with emerging functions in mammalian neurodevelopment and human neurodevelopmental diseases. The mechanisms controlling autophagy in neuronal development are not fully understood. Here, we found that conditional deletion of the Forkhead Box O transcription factors FoxO1, FoxO3, and FoxO4 strongly impaired autophagic flux in developing neurons of the adult mouse hippocampus. Moreover, FoxO deficiency led to altered dendritic morphology, increased spine density, and aberrant spine positioning in adult-generated neurons. Strikingly, pharmacological induction of autophagy was sufficient to correct abnormal dendrite and spine development of FoxO-deficient neurons. Collectively, these findings reveal a novel link between FoxO transcription factors, autophagic flux, and maturation of developing neurons.
EVALuna2:34732

In vivo targeting of adult neural stem cells in the dentate gyrus by a split-cre approach - Beckervordersandforth, Ruth; Deshpande, Aditi; Schäffner, Iris; Huttner, Hagen; Lepier, Alexandra; Lie, Dieter Chichung; Goetz, Magdalena (Stem Cell Reports, 2014)
We describe the labeling of adult neural stem cells (aNSCs) in the mouse and human dentate gyrus (DG) by the combinatorial expression of glial fibrillary acidic protein (GFAP) and Prominin1, as revealed by immunohistochemistry. Split-Cre-based genetic fate mapping of these double-positive cells in the adult murine DG reveals their NSC identity, as they are self-renewing and contribute to neurogenesis over several months. Their progeny reacts to stimuli such as voluntary exercise with increased neurogenesis. Prominin1+/GFAP+ cells also exist in the adult human DG, the only region in the human brain for which adult neurogenesis has been consistently reported. Our data, together with previous evidence of such double-positive NSCs in the developing murine brain and in neurogenic regions of vertebrates with widespread neurogenesis, suggest that Prominin1- and GFAP-expressing cells are NSCs in a wide range of species in development and adulthood.
EVALuna2:22282

Mitochondrial Dysfunction in Astrocytes Impairs the Generation of Reactive Astrocytes and Enhances Neuronal Cell Death in the Cortex Upon Photothrombotic Lesion - Fiebig, Christian; Keiner, Silke; Ebert, Birgit; Schäffner, Iris; Jagasia, Ravi; Lie, Dieter Chichung; Beckervordersandforth, Ruth (Frontiers in Molecular Neuroscience, 2019)
Mitochondria are key organelles in regulating the metabolic state of a cell. In the brain, mitochondrial oxidative metabolism is the prevailing mechanism for neurons to generate ATP. While it is firmly established that neuronal function is highly dependent on mitochondrial metabolism, it is less well-understood how astrocytes function rely on mitochondria. In this study, we investigate if astrocytes require a functional mitochondrial electron transport chain (ETC) and oxidative phosphorylation (oxPhos) under physiological and injury conditions. By immunohistochemistry we show that astrocytes expressed components of the ETC and oxPhos complexes in vivo. Genetic inhibition of mitochondrial transcription by conditional deletion of mitochondrial transcription factor A (Tfam) led to dysfunctional ETC and oxPhos activity, as indicated by aberrant mitochondrial swelling in astrocytes. Mitochondrial dysfunction did not impair survival of astrocytes, but caused a reactive gliosis in the cortex under physiological conditions. Photochemically initiated thrombosis induced ischemic stroke led to formation of hyperfused mitochondrial networks in reactive astrocytes of the perilesional area. Importantly, mitochondrial dysfunction significantly reduced the generation of new astrocytes and increased neuronal cell death in the perilesional area. These results indicate that astrocytes require a functional ETC and oxPhos machinery for proliferation and neuroprotection under injury conditions.
CRIS-Team WoS Importer:2019-03-06

Mitochondria modify exercise-induced development of stem cell-derived neurons in the adult brain - Steib, Kathrin; Schäffner, Iris; Jagasia, Ravi; Ebert, Birgit; Lie, Dieter Chichung (The Journal of Neuroscience, 2014)
Neural stem cells in the adult mammalian hippocampus continuously generate new functional neurons, which modify the hippocampal network and significantly contribute to cognitive processes and mood regulation. Here, we show that the development of new neurons from stem cells in adult mice is paralleled by extensive changes to mitochondrial mass, distribution, and shape. Moreover, exercise-a strong modifier of adult hippocampal neurogenesis-accelerates neuronal maturation and induces a profound increase in mitochondrial content and the presence of mitochondria in dendritic segments. Genetic inhibition of the activity of the mitochondrial fission factor dynamin-related protein 1 (Drp1) inhibits neurogenesis under basal and exercise conditions. Conversely, enhanced Drp1 activity furthers exercise-induced acceleration of neuronal maturation. Collectively, these results indicate that adult hippocampal neurogenesis requires adaptation of the mitochondrial compartment and suggest that mitochondria are targets for enhancing neurogenesis-dependent hippocampal plasticity.
EVALuna2:26325

Phosphorylation of the neurogenic transcription factor SOX11 on serine 133 modulates neuronal morphogenesis - Balta, Elli-Anna; Schäffner, Iris; Wittmann, Marie-Theres; Sock, Elisabeth; Von Zweydorf, Felix; von Wittgenstein, Julia; Steib, Kathrin; Heim, Birgit; Kremmer, Elisabeth; Häberle, Benjamin; Ueffing, Marius; Lie, Dieter Chichung; et al. (Scientific Reports, 2018)
The intellectual disability gene, Sox11, encodes for a critical neurodevelopmental transcription factor with functions in precursor survival, neuronal fate determination, migration and morphogenesis. The mechanisms regulating SOX11's activity remain largely unknown. Mass spectrometric analysis uncovered that SOX11 can be post-translationally modified by phosphorylation. Here, we report that phosphorylatable serines surrounding the high-mobility group box modulate SOX11's transcriptional activity. Through Mass Spectrometry (MS), co-immunoprecipitation assays and in vitro phosphorylation assays followed by MS we verified that protein kinase A (PKA) interacts with SOX11 and phosphorylates it on S133. In vivo replacement of SoxC factors in developing adult-generated hippocampal neurons with SOX11 S133 phospho-mutants indicated that phosphorylation on S133 modulates dendrite development of adult-born dentate granule neurons, while reporter assays suggested that S133 phosphorylation fine-tunes the activation of select target genes. These data provide novel insight into the control of the critical neurodevelopmental regulator SOX11 and imply SOX11 as a mediator of PKA-regulated neuronal development.
EVALuna2:35738

Role of Mitochondrial Metabolism in the Control of Early Lineage Progression and Aging Phenotypes in Adult Hippocampal Neurogenesis - Beckervordersandforth, Ruth; Ebert, Birgit; Schäffner, Iris; Moss, Jonathan; Fiebig, Christian; Shin, Jaehoon; Moore, Darcie L.; Ghosh, Laboni; Trinchero, Mariela F.; Stockburger, Carola; Friedland, Kristina; Steib, Kathrin; et al. (Neuron, 2017)
EVALuna2:4763

Sox11 is an Activity-Regulated Gene with Dentate-Gyrus-Specific Expression Upon General Neural Activation - von Wittgenstein, Julia; Zheng, Fang; Wittmann, Marie-Theres; Balta, Elli-Anna; Ferrazzi, Fulvia; Schäffner, Iris; Häberle, Benjamin; Valero Aracama, Maria Jesus; Koehl, Muriel; Miranda, Carlos J.; Kaspar, Brian K.; Ekici, Arif Bülent; et al. (Cerebral Cortex, 2020)
Neuronal activity initiates transcriptional programs that shape long-term changes in plasticity. Although neuron subtypes differ in their plasticity response, most activity-dependent transcription factors (TFs) are broadly expressed across neuron subtypes and brain regions. Thus, how region- and neuronal subtype-specific plasticity are established on the transcriptional level remains poorly understood. We report that in young adult (i.e., 6-8 weeks old) mice, the developmental TF SOX11 is induced in neurons within 6 h either by electroconvulsive stimulation or by exploration of a novel environment. Strikingly, SOX11 induction was restricted to the dentate gyrus (DG) of the hippocampus. In the novel environment paradigm, SOX11 was observed in a subset of c-FOS expressing neurons (ca. 15%); whereas around 75% of SOX11+ DG granule neurons were c-FOS+, indicating that SOX11 was induced in an activity-dependent fashion in a subset of neurons. Environmental enrichment or virus-mediated overexpression of SOX11 enhanced the excitability of DG granule cells and downregulated the expression of different potassium channel subunits, whereas conditional Sox11/4 knock-out mice presented the opposite phenotype. We propose that Sox11 is regulated in an activity-dependent fashion, which is specific to the DG, and speculate that activity-dependent Sox11 expression may participate in the modulation of DG neuron plasticity.
CRIS-Team Scopus Importer:2020-05-29
Keywords: dentate gyrus; hippocampus; immediate early gene; plasticity; Sox11

Structural and functional rejuvenation of the aged brain by an approved anti-asthmatic drug - Marschallinger, Julia; Schäffner, Iris; Klein, Barbara; Gelfert, Renate; Rivera, Francisco J.; Illes, Sebastian; Grassner, Lukas; Janssen, Maximilian; Rotheneichner, Peter; Schmuckermair, Claudia; Coras, Roland; Boccazzi, Marta; et al. (Nature Communications, 2015)
As human life expectancy has improved rapidly in industrialized societies, age-related cognitive impairment presents an increasing challenge. Targeting histopathological processes that correlate with age-related cognitive declines, such as neuroinflammation, low levels of neurogenesis, disrupted blood-brain barrier and altered neuronal activity, might lead to structural and functional rejuvenation of the aged brain. Here we show that a 6-week treatment of young (4 months) and old (20 months) rats with montelukast, a marketed anti-asthmatic drug antagonizing leukotriene receptors, reduces neuroinflammation, elevates hippocampal neurogenesis and improves learning and memory in old animals. By using gene knockdown and knockout approaches, we demonstrate that the effect is mediated through inhibition of the GPR17 receptor. This work illustrates that inhibition of leukotriene receptor signalling might represent a safe and druggable target to restore cognitive functions in old individuals and paves the way for future clinical translation of leukotriene receptor inhibition for the treatment of dementias.
EVALuna2:7294

β-catenin signaling modulates the tempo of dendritic growth of adult-born hippocampal neurons - Heppt, Jana; Wittmann, Marie-Theres; Schäffner, Iris; Billmann, Charlotte; Zhang, Jingzhong; Vogt-Weisenhorn, Daniela; Prakash, Nilima; Wurst, Wolfgang; Taketo, Makoto Mark; Lie, Dieter Chichung (EMBO Journal, 2020)
In adult hippocampal neurogenesis, stem/progenitor cells generate dentate granule neurons that contribute to hippocampal plasticity. The establishment of a morphologically defined dendritic arbor is central to the functional integration of adult-born neurons. We investigated the role of canonical Wnt/β-catenin signaling in dendritogenesis of adult-born neurons. We show that canonical Wnt signaling follows a biphasic pattern, with high activity in stem/progenitor cells, attenuation in immature neurons, and reactivation during maturation, and demonstrate that this activity pattern is required for proper dendrite development. Increasing β-catenin signaling in maturing neurons of young adult mice transiently accelerated dendritic growth, but eventually produced dendritic defects and excessive spine numbers. In middle-aged mice, in which protracted dendrite and spine development were paralleled by lower canonical Wnt signaling activity, enhancement of β-catenin signaling restored dendritic growth and spine formation to levels observed in young adult animals. Our data indicate that precise timing and strength of β-catenin signaling are essential for the correct functional integration of adult-born neurons and suggest Wnt/β-catenin signaling as a pathway to ameliorate deficits in adult neurogenesis during aging.
CRIS-Team Scopus Importer:2020-09-25
Keywords: adult neurogenesis; aging; dendrite; hippocampus; Wnt signaling